How to Protect and Promote the Nutrition of Mothers and Children : Case Studies in Latin America and the Caribbean - World Bank (World Bank, Washington, DC, 2016)
The nutrition cluster is a very important entity to coordinate actions during emergencies. It is important that the nutrition cluster know in advance which institutions work where and what kind of inputs are pre-positioned. Risk management plans need to be ready at the local level in advance of emergencies. Although emergencies occur every year in Guatemala, the emergency response often fails to incorporate the management of malnutrition among its priority actions. Community programs, like AIN-C (a community- based child care program - atencion integral a la ninez comunitaria), can be an efficient mechanism to protect young children's nutrition and provide an important channel for the government or other assistance agencies to funnel support to communities in need during a period of crisis or emergency. This is because community workers know the families and those who are most vulnerable; they are willing to be called upon to help their community; and they can provide educational support to families to ensure rapid recovery among young children. Community-based growth promotion programs such as AIN-C can be strengthened and scaled up, and they are a good investment, in the aftermath of an emergency or during a time of economic crisis, to swiftly deliver services to affected families. Community agents can carry important information to the community and can distribute food, nutrition and health supplements such as micronutrient powders and oral rehydration salts for young children, as well as hygiene and water purification products. Community kitchens are an efficient approach to reduce hunger among the poor during times of high economic stress. They provide a social safety net and can have a nutrition effect when carefully planned. Community kitchens adjust to the labor market and general economic conditions; hence targeting of the poor and most in need through community kitchens is self-selective. The kitchens can expand and shrink as participants continually assess the trade-off between unpaid work in exchange for free or inexpensive meals and the pursuit of opportunities in the labor market.